PENGARUH BUDAYA ORGANISASI BEBAN KERJA DAN DISIPLIN KERJA MELALUI KEPUASAN KERJA DALAM MEMENGARUHI KINERJA PENGAWAI DI DINAS SOSIAL KABUPATEN SITUBONDO - Mu’ad, Muhammad; Pramesthi, Riska Ayu; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2024)
The aim of the research is to determine the influence of organizational culture, workload and work discipline through job satisfaction in influencing employee performance in the Situbondo Regency Social Service. The sampling technique used in this research was a saturated sample with a sample size of 30 employees. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Organizational Culture has a negative but not significant effect on job satisfaction, Workload has a positive but not significant effect on job satisfaction, Work discipline has a negative but not significant effect on job satisfaction, Organizational Culture has a positive effect but not significant on Performance, Workload has a significant positive effect on Performance, Work discipline has a Significant Negative effect on Performance, Job satisfaction has a positive but not significant effect on Performance, Organizational Culture has a negative but not significant effect on Performance through Job Satisfaction, Workload has a positive but not significant effect not significant on performance through job satisfaction, work discipline has a negative but not significant effect on performance through job satisfaction.